Structural Homology Modelling, Molecular Docking and Initial Insight into Phenol Degradation Activity of Recombinant Tyrosinase from Lentinula edodes Mushroom: Structure and Phenol Decontamination by Lentinula edodes Tyrosinase - David, Viaevanilly; Abdul Rasah, Mohd Nasir; Lindang, Herman Umbau; Mokhtar, Ruzaidi Azli Mohd; Seelan, Jaya Seelan Sathiya; Razali, Rafida; Budiman, Cahyo (Journal of Tropical Life Science, 2026)
Tyrosinase is a copper-containing enzyme known for ability to degrade phenolic compounds, making it highly attractive for industrial applications, particularly in wastewater decontamination. While fungal tyrosinase is considered an excellent source for enzyme studies and applications, deeper investigations into its structural properties and phenol degradation activity are still needed. This study aims to elucidate the structural properties of tyrosinase from the mushroom Lentinula edodes (Edo-Tyr) and evaluate its phenol degradation activity. The amino acid sequence of Edo-Tyr was retrieved from GenBank (AB 033993.1) and used to construct three-dimensional models via Robetta, SWISS-MODEL, and Phyre2. The best model obtained from SWISS-MODEL indicated that the structure is predominantly helical, with a Cu2+ ion observed in the active site coordinated by His64, His90, His99, His261, His165, His289, and His290. Structural comparisons revealed similarity between Edo-Tyr and tyrosinase from Bacillus megaterium (Bm-Tyr), with an R.M.S.D of 1.38 Å. Sequence alignment further suggested that His265 serves as the active site in Edo-Tyr, analogous to His208 in Bm-Tyr. Molecular docking analysis demonstrated that the catalytic mechanism of Edo-Tyr likely involves hydroxylation via an electrophilic attack, potentially facilitated by a tyrosine rotation event. Key residues implicated in this process include His64, His265, His90, Pro277, and Asp262. Subsequent in vitro assays using a phenol solution confirmed the recombinant Edo-Tyr's ability to degrade phenol, achieving a 48% reduction in phenol concentration with 0.3 U/µL of tyrosinase. These findings confirm the potential application of Edo-Tyr in bioremediation, specifically for phenol decontamination, highlighting its promise for industrial and environmental applications.